Is it complex environments or complex systems that undermines police reform in developing countries?. (4th July 2018) - Baker, Bruce
Abstract: This article is a reflection upon the challenges facing police reform in developing countries. In doing so it explores the usefulness of complexity theory both to understand the evidence of relative failure and to reconsider the explanations offered for that failure in terms of unique individual factors or the complex nature of the environment. The article suggests that the nature of police organisations as complex social systems may be a principal reason for failure. The article outlines some of the key features of complex systems and illustrates these from actual police reform. The article then turns to whether complexity theory can be of any practical use in police reform programmes. It concludes that greater success may be forthcoming if the insights of complexity theory are taken on board by reformers.